Asian-Canadian children and families involved in the child welfare system in Canada: A mixed methods study. (August 2017) - Lee, Barbara; Fuller-Thomson, Esme; Fallon, Barbara; Trocmé, Nico; Black, Tara
Abstract: Objective: The purpose of the study is to understand the similarities and differences in child welfare involvement for Asian- Canadian (East and Southeast Asian) versus White-Canadian children and families involved in the child welfare system in Canada, and to consider the implications and recommendations for service. This mixed methods study began by replicating this author's previous study that found significant differences in the case characteristics and services used by Asian compared to non-Asian families in the child welfare system. The present study used a mixed method approach to further build a comprehensive descriptive understanding of Asian-Canadian children and families involved in the child welfare system at national and local levels. Methods: Secondary data analysis of the 2008 Canadian Incidence Study of Reported Child Abuse and Neglect (CIS-2008) was conducted to identify the case characteristics (such as referral source, investigation type, and primary maltreatment type) and short-term service outcome (such as substantiation decision and decision to transfer to ongoing child protection services) of child maltreatment investigations involving Asian-Canadian children and families in the child welfare system. The results were presented to focus group participants in a workshop, and a semi-structured interview guide was used to document child welfare workers' experience with and perception of Asian-Canadian service users. Results: The results indicated substantial differences between Asian- Canadian and White-Canadian children and families investigated by child welfare agencies in respect to the household composition, maltreatment type, substantiation decision and decision to transfer to ongoing child protection services. Child welfare workers validated the results from secondary data analysis of the CIS-2008 and offer a broader cultural and structural context for understanding child welfare involvement with Asian-Canadians. Conclusion: Asian-Canadian children and families bring a diversity of cultural values and family norms. This study prompts further consideration for social work practice and policies in working with Asian-Canadian children and families involved in the child welfare system.